2016
DOI: 10.1158/1940-6207.capr-15-0069
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Drug-Metabolizing Polymorphisms and Smoking Predict Recurrence of Non–Muscle-Invasive Bladder Cancer: A Gene–Smoking Interaction

Abstract: Cigarette smoking is the most important known risk factor for urinary bladder cancer. Selected arylamines in cigarette smoke are recognized human bladder carcinogens and undergo biotransformation through several detoxification pathways, such as the glutathione S-transferases (GST), and uridinediphospho-glucuronosyltransferases (UGT) pathways. GSTM1 deletion status and UGT1A1Ã 28 rs8175347 genotypes were assessed in 189 non-muscle-invasive bladder cancers (NMIBC) patients with pTa (77.2%) and pT1 (22.8%) tumors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
6
0
3
Order By: Relevance
“…Mutations in the UGT1A cluster, located in 2q37.1, have been associated with UBC in previous genetic studies [3, 4, 21, 22], SNPs in UGT1A have shown both harmful [21] and protective effects for the risk of developing de novo UBC [4, 22], but there is uncertainty if UGT1A influences the disease course, especially in NMIBC. Lacombe et al evaluated the effect of UGT1A1*28 SNP rs8175347 in a group of 189 NMIBC cases [23] and concluded that it significantly increased the risk of recurrence, with a gene-smoking interaction present (higher recurrence risk for ever smokers). Nevertheless, the many strata in the study resulted in small subgroup sample sizes [23]; therefore, the findings must be replicated in other cohorts to establish validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the UGT1A cluster, located in 2q37.1, have been associated with UBC in previous genetic studies [3, 4, 21, 22], SNPs in UGT1A have shown both harmful [21] and protective effects for the risk of developing de novo UBC [4, 22], but there is uncertainty if UGT1A influences the disease course, especially in NMIBC. Lacombe et al evaluated the effect of UGT1A1*28 SNP rs8175347 in a group of 189 NMIBC cases [23] and concluded that it significantly increased the risk of recurrence, with a gene-smoking interaction present (higher recurrence risk for ever smokers). Nevertheless, the many strata in the study resulted in small subgroup sample sizes [23]; therefore, the findings must be replicated in other cohorts to establish validity.…”
Section: Discussionmentioning
confidence: 99%
“…Lacombe et al evaluated the effect of UGT1A1*28 SNP rs8175347 in a group of 189 NMIBC cases [23] and concluded that it significantly increased the risk of recurrence, with a gene-smoking interaction present (higher recurrence risk for ever smokers). Nevertheless, the many strata in the study resulted in small subgroup sample sizes [23]; therefore, the findings must be replicated in other cohorts to establish validity.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is a known risk factor for bladder cancer [ 113 ], and the products of GSTs help detoxify the polycyclic aromatic hydrocarbons found in tobacco smoke [ 114 ]. Our study suggests that the GSTM1-null genotype might play a role in such detoxification, but the GSTT1-null genotype does not.…”
Section: Discussionmentioning
confidence: 99%
“…Their main function being to transfer the acetyl group from AcCoA onto the nitrogen or oxygen atom in such substances such as arylamines (17), hydrazines (18), arylhydroxylamines (19) or arylhydrazines (17). These enzymes play an important role in the metabolism of drugs (20) and toxins as well as in detoxification (21,22). Using 2-AF as an example, the process by which arylamines cause cancer is as follows: first, NATs in the cell transform 2-AF into N-acetyl-2-aminofluorene (2-AAF) (23), then 2-AAF is further activated by other enzymes such as glucuronyltransferase, deacylase, sulfotransferase and acyltransferase (24,25), and ultimately transformed in the end to carcinogens nitrenium ion and arylamidonium ion.…”
Section: Discussionmentioning
confidence: 99%